Antipsychotic Cardiometabolic Side Effect Monitoring in a State Community Mental Health System. - Cotes, Robert; Nesnera, Alex; Kelly, Michael; Orsini, Karen; Xie, Haiyi; McHugo, Greg; Bartels, Stephen; Brunette, Mary (Community Mental Health Journal, 2015)
Antipsychotic medications can cause serious cardiometabolic side effects. No recent research has broadly evaluated monitoring and strategies to improve monitoring in U.S. public mental health systems. To address this knowledge gap, we evaluated education with audit and feedback to leaders to improve cardiometabolic monitoring in a state mental health system. We used Chi square statistics and logistic regressions to explore changes in monitoring recorded in randomly sampled records over 2 years. In 2009, assessment of patients on antipsychotics was 29.6 % for cholesterol, 40.4 % for glucose, 29.1 % for triglycerides, 54.3 % for weight, 33.6 % for blood pressure, and 5.7 % for abdominal girth. In 2010, four of ten mental health centers improved their rate of adult laboratory monitoring. Overall monitoring in the state did not increase. Education for prescribers with audit and feedback to leaders can improve monitoring in some settings, but more intensive and/or prolonged interventions may be required.